Factors that influence perceived service quality among Port Klang Trading client / Atira Adlan and Asmaa’ Arinah Zulkifli - Adlan, Atira; Zulkifli, Asmaa’ Arinah (Faculty of Business and Management, 2015)
Service quality is crucial for every logistic company to consider in order to expand their business in the market. The development of technology has leads to business activity. However, lack of service quality had been identify as the major barriers for logistic company to expand their business. Factors that influenced service quality had been discuss by several researchers. This research had identify the factors that influence perceived service quality among Port Klang Trading client and had come out with recommendations that the company used in order to enhance the current service quality. This descriptive study used survey method in data collection. These data was collected using questionnaire that had been distributed to the respondent. Data is gathered using a cross-sectional study due to the fact that these data was collected once and not continuously. The sample size for this research were 80 respondents from the Port Klang Trading client out of 100 total population. These respondents were being selected through cluster sampling technique from five departments in the company. The basis of the research was based on Servqual theory by Parasuraman (2009) which were reliability, assurance, tangibility, empathy and responsiveness. In particular, this research provided an insight regarding factors that influence service quality towards Port Klang Trading Company